2018
DOI: 10.5114/aoms.2017.69147
|View full text |Cite
|
Sign up to set email alerts
|

High lncRNA HULC expression is associated with poor prognosis and promotes tumor progression by regulating epithelial-mesenchymal transition in prostate cancer

Abstract: IntroductionRecently, increasing evidence has shown that long non-coding RNAs (lncRNAs) play critical roles in tumor progression and development. However, the expression pattern and biological function of lncRNA HULC (highly upregulated in liver cancer) in prostate cancer (PCa) remain largely unclear.Material and methodsThe expression of lncRNA HULC in 53 paired PCa tissues and cell lines was detected by quantitative real-time polymerase chain reaction (qRT-PCR). The χ2 test was used to explore the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Furthermore, miRNAs are capable of regulating the occurrence and development of the nervous system, and some specific miRNAs can regulate the pathophysiological processes of neurological diseases. For example, miR‐183 has been reported to share a close association with the occurrence of glioma, miRNA‐129‐2‐3p and miRNA‐935 are expressed in plasma and brain tissues of intractable epilepsy, and miR‐323a‐5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miRNAs are capable of regulating the occurrence and development of the nervous system, and some specific miRNAs can regulate the pathophysiological processes of neurological diseases. For example, miR‐183 has been reported to share a close association with the occurrence of glioma, miRNA‐129‐2‐3p and miRNA‐935 are expressed in plasma and brain tissues of intractable epilepsy, and miR‐323a‐5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia …”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-183 has been reported to share a close association with the occurrence of glioma, miRNA-129-2-3p and miRNA-935 are expressed in plasma and brain tissues of intractable epilepsy, and miR-323a-5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia. [28][29][30][31] Evidence has been provided that miR-135a-5p can inhibit tumor cell proliferation and promote the apoptosis of tumor cells in many tumors, while its role in epilepsy has yet to be adequately identified. 32 Reports have suggested that miR-135a-5p confer neuronal protection in mice with Alzheimer's disease by regulating potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…HULC has been studied in several cancers and promotes tumorigenesis [1][2][3][4]. Furthermore, HULC polymorphisms are associated with hepatocellular cancer risk and prognosis [5,6]. In addition, HULC enhances autophagy [7] and facilitates hepatocellular carcinoma genesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidences have shown that lncRNAs are involved in regulating various biological characteristics of tumors, including proliferation, apoptosis, metastasis, and metabolism [13,14]. Previous microarray results showed that a large number of lncRNAs were significantly downregulated or upregulated in different cancer tissues [15,16]. lncRNAs are also involved in the occurrence and development of RCC, such as knockdown of lncRNA ROR inhibiting the proliferation, migration, and invasion of RCC cells.…”
Section: Introductionmentioning
confidence: 99%